2008
DOI: 10.1111/j.1744-7429.2008.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Rain Forests are not Havens for Reptile Species in Tropical Mexico

Abstract: A widely accepted biodiversity crisis in the tropics has been recently challenged by claims that secondary forests will gradually restore biodiversity losses. This prediction was examined for the herpetofauna in Quintana Roo, Mexico. Quantitative sampling (108 transects) of reptiles was undertaken monthly (January-September 2004) along a vegetation gradient covering induced grasslands, and regrowth and primary rain forests. A total of 35 species was found, 14 being present in and five showing dependence on mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
1
27
0
3
Order By: Relevance
“…In this sense, species that occurred in both inside and outside of the reserve were of the genus Sceloporus, which showed tolerance for the transformed environments due to physiological advantages as impermeable skin or high tolerance to aridity, use a high diversity of environments, and diversity of habits (e.g., saxicolous, arboreal; Macip-Ríos and Muñoz-Alonso 2008). These patterns have been promoted by heterogeneous environments that are reflected in a high number of microhabitats, such as logs, rocks, holes, accumulated rocks, left litter, open areas, which in turn will generate perch sites (Luja et al 2008). These conditions are favorable to S. utiformis and A. nebulosus because they were dominant species in both inside and outside the reserve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, species that occurred in both inside and outside of the reserve were of the genus Sceloporus, which showed tolerance for the transformed environments due to physiological advantages as impermeable skin or high tolerance to aridity, use a high diversity of environments, and diversity of habits (e.g., saxicolous, arboreal; Macip-Ríos and Muñoz-Alonso 2008). These patterns have been promoted by heterogeneous environments that are reflected in a high number of microhabitats, such as logs, rocks, holes, accumulated rocks, left litter, open areas, which in turn will generate perch sites (Luja et al 2008). These conditions are favorable to S. utiformis and A. nebulosus because they were dominant species in both inside and outside the reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Amphibians and reptiles were searched for during the hikes by checking all habitats and microhabitats types, such as under rocks and logs and within litter, holes, and crevices (Casas-Andreu et al 1991). In order to avoid pseudoreplication we did not sample in the same site more than a single time (Luja et al 2008). The first five specimens each species observed in the field were collected by hand or herpetological hooks in case of individuals of genus Crotalus, to be identified based on our experience or with dichotomous keys, and each specimen was photographed, which photographs were housed at Texas University in Arlington (UTADC).…”
Section: Fieldworkmentioning
confidence: 99%
“…Most studies were so far conducted in the neotropics and showed that, if canopy cover is high and natural habitat is sufficiently close, secondary habitats (such as coffee and cacao agroforest ecosystems) can sustain herpetological diversity (Pineda et al 2005;Suazo-Ortuo et al 2008). As open canopy alters the climatic regime in the plantation (Stratford and Robinson 2005), temperature is most likely limiting forest specialists in these habitats (Perfecto et al 2007, Luja et al 2008. Comparable studies from Southeast Asia are still scarce.…”
Section: Amphibians and Reptilesmentioning
confidence: 99%
“…On a longtemps considéré que le développement d'une forêt secondaire favorisait le renouvellement des espèces forestières et le maintien de la bio diversité. Cette idée est désormais contestée [4]. Luja et al [4] évaluent à 70 % au moins la réduction du nombre d'espèces et de la densité de serpents dans les forêts secondaires du sud du Mexique ou en savane herbeuse, par rapport aux chiffres observés dans la forêt primaire.…”
Section: Repèresunclassified
“…Cette idée est désormais contestée [4]. Luja et al [4] évaluent à 70 % au moins la réduction du nombre d'espèces et de la densité de serpents dans les forêts secondaires du sud du Mexique ou en savane herbeuse, par rapport aux chiffres observés dans la forêt primaire. En revanche, en zone découverte, le Bothrops asper -crotale particulièrement venimeux -devient l'espèce majoritaire alors qu'elle est minoritaire en forêt.…”
Section: Repèresunclassified